2014
DOI: 10.3414/me13-02-0032
|View full text |Cite
|
Sign up to set email alerts
|

Adaptable Healing Patient Room for Stroke Patients

Abstract: SummaryIntroduction: This article is part of the Focus Theme of Methods of Information in Medicine on “Pervasive Intelligent Technologies for Health”.Background: This paper addresses the evaluation with hospital staff of an in-patient environment that supports patients, family, nursing staff and medical specialists during the recovery process of neurology patients and especially patients recovering from a stroke. We describe the methods that were used to evaluate the Adaptive Daily Rhythm Atmospheres (ADRA), A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…26 27 One study explored staff opinion about the potential value of adaptable healing rooms (AHRs) for patients who had experienced a stroke. 28 These specialised bedroom designs used timed lighting and multimedia technology to provide targeted levels of light and noise throughout the day, orientation information (eg, clock and timetable) and positive distraction (eg, family photos or nature scenes) for the patient. Staff suggested that AHRs may help to facilitate healing by promoting patient/staff relationships, being patient centred, helping patients to wake up naturally and improving sleep, providing more information and structure to the day and providing stimulation at the right times.…”
Section: Patient Clinical Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…26 27 One study explored staff opinion about the potential value of adaptable healing rooms (AHRs) for patients who had experienced a stroke. 28 These specialised bedroom designs used timed lighting and multimedia technology to provide targeted levels of light and noise throughout the day, orientation information (eg, clock and timetable) and positive distraction (eg, family photos or nature scenes) for the patient. Staff suggested that AHRs may help to facilitate healing by promoting patient/staff relationships, being patient centred, helping patients to wake up naturally and improving sleep, providing more information and structure to the day and providing stimulation at the right times.…”
Section: Patient Clinical Outcomesmentioning
confidence: 99%
“…Staff suggested that AHRs may help to facilitate healing by promoting patient/staff relationships, being patient centred, helping patients to wake up naturally and improving sleep, providing more information and structure to the day and providing stimulation at the right times. 28 Expert elicitation conducted with a large stakeholder group of people who had experienced a stroke and staff, researchers, architects, designers and policy makers 29 revealed four agreed 'fundamentally important'…”
Section: Patient Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there have only been a few academic randomized controlled trial (RCT) studies that actually utilized sunlight therapy to treat PSD patients. In a prospective study by the Daemen et al. (2014) and Danish researchers West et al., 2017a , West et al., 2017b , since bedridden stroke patients were indoors and could not be exposed to the natural daytime variation, naturalistic lighting that mimicked the natural daytime spectrum variation was installed in the experimental unit, while standard artificial lighting was installed in the control unit.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, healthcare facilities were created to be functionally effective and are not necessarily suited to the psychological needs of patients and their families (Ulrich, 1991). Hospital patient rooms, where patients spend most of their time (Blennerhassett, Borschmann, Lipson-Smith, & Bernhardt, 2018), are usually highly institutionalized environments that are not adaptable to individual patient needs (Daemen, Flinsenberg, et al, 2014). Patients' experiences in healthcare facilities are generally characterized by fear and anxiety (Dijkstra, 2009).…”
mentioning
confidence: 99%